Cloud Computing Security and Privacy Preservation: Using multi-level encryption (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Cloud computing has grown very quickly to become a promising business idea in the IT industry due to its characteristics such as cost reduction, flexibility, convenience, and scalability. The wide spread of Cloud Computing was accompanied by research fields in many aspects such as performance, storage, retrieval speed, backup and restore, security and privacy and other aspects related to it, which are still searched for today. Security and Privacy of data in Cloud Computing is of utmost importance to all its users, regardless of the nature of the stored data. In this paper, we propose a system that is secure and computationally efficient. The system focuses on three algorithms are AES (Advanced Encryption Algorithm), Blowfish algorithm and MD5 algorithm to build our proposed system. The principle goal guiding the design of any encryption algorithm must be security against unauthorized attacks and our proposed system is more security than any algorithm else. However, for all practical applications, cost of implementation and performance are also major concerns.